INDIGENOUS PLANT- DERIVED MEDICINES USED FOR GASTROINTESTINAL DISORDERS IN LIMPOPO PROVINCE, SOUTH AFRICA - Sejabaledi A. Rankoana (Social Sciences, Humanities and Education Journal (SHE Journal), 2022)
The results reported in this research are part of a medical ethnobotanical study undertaken between 2012 and 2019 in Limpopo Province, South Africa. Eighty-nine plant species were identified as potential sources of medicine. Of these plants, 21 species from 18 botanical families were used medicinally to treat gastrointestinal diseases such as diarrhea, stomachaches, dysentery, and constipation. The plants provide medicinal infusions, decoctions, saps, and powders that are used orally to treat these disorders. Three of the plants used, Dombeya rotundifolia, Siphinochilus aethiopicus, and Trichilia emetica, treat many gastrointestinal disorders, the most common of which being dysentery. The research demonstrates that knowledge of indigenous plant-derived medicines is not limited to traditional health practitioners, since ordinary community members administer the medications without consultation with medical specialists beforehand. This form of primary health care might be documented and disseminated in order to enhance the community's health and well-being through the utilization of indigenous and culturally distinctive resources.